2018
DOI: 10.3389/fpsyg.2018.00405
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Handedness, Sex, and Cognitive Abilities on Left–Right Discrimination: A Behavioral Study

Abstract: The present study examined the relationship between left–right discrimination (LRD) performance and handedness, sex and cognitive abilities. In total, 31 men and 35 women – with a balanced ratio of left-and right-handers – completed the Bergen Left–Right Discrimination Test. We found an advantage of left-handers in both identifying left hands and in verifying “left” propositions. A sex effect was also found, as women had an overall higher error rate than men, and increasing difficulty impacted their reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(107 reference statements)
1
8
0
Order By: Relevance
“…Females tend to outperform males in most memory tasks [23]. However, this is a complex dynamic, as recent research suggests that sex may interact with handedness on cognition, with reduced brain lateralization in women explaining lower cognition in select cognitive parameters [24]. Relatedly, in a large cross-sectional study of older adults and based on grip strength, left-handed women scored worse than right-handed women in immediate and delayed memory [12].…”
Section: Introductionmentioning
confidence: 99%
“…Females tend to outperform males in most memory tasks [23]. However, this is a complex dynamic, as recent research suggests that sex may interact with handedness on cognition, with reduced brain lateralization in women explaining lower cognition in select cognitive parameters [24]. Relatedly, in a large cross-sectional study of older adults and based on grip strength, left-handed women scored worse than right-handed women in immediate and delayed memory [12].…”
Section: Introductionmentioning
confidence: 99%
“…Left-handed mail participants were found performing the Bergen left-right discrimination better than right-hander males, however this was sex-depended effect while the effect of handedness was found insignificant in the total number of male and female participants [20]. No difference in the left right discrimination between the left-handed and right-handed people was found in other studies as well [21][22][23][24].…”
Section: Introductionmentioning
confidence: 70%
“…Generally, people have right-hemispheric spatial dominance and left-hemispheric language dominance, but left-handed or ambidextrous people may have atypical lateralization ( Szaflarski et al, 2002 ). Our studies included only right-handed participants as previous studies suggested that left-handed people had advantage ( Constant and Mellet, 2018 ) or disadvantage ( Hannay et al, 1990 ) in right-left discrimination compared to right-handers. We may be able to reveal whether and how handedness affects right-left discrimination by considering the two processes and cortical lateralization.…”
Section: Discussionmentioning
confidence: 99%
“…All participants reported no history of neurological and psychiatric illness. We analyzed data from the 98 participants who reported they were right-handed to control potentially confounding effect of handedness ( Hannay et al, 1990 ; Constant and Mellet, 2018 ). Written informed consent was obtained from each participant.…”
Section: Studymentioning
confidence: 99%